FOXP2 down expression is associated with executive dysfunctions and electrophysiological abnormalities of brain in Autism spectrum disorder; a neuroimaging genetic study. (September 2022) - Haghighatfard, Arvin; Yaghoubi asl, Elham; Bahadori, Rosita Azar; Aliabadian, Rojina; Farhadi, Mahdi; Mohammadpour, Fatemeh; Tabrizi, Zeinab
Background and aims: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by language impairment, and challenges with social interaction, communication, and repetitive behaviors. Although genetics are a primary cause of ASD, the exact genes and molecular mechanisms involved in its pathogenesis are not completely clear. The FOXP2 gene encodes a transcription factor that is known for its major role in language development and severe speech problems. The present study aimed to evaluate the role of FOXP2 in ASD etiology, executive functions, and brain activities. Methods: In the present study, we recruited 450 children with ASD and 490 neurotypical control children. Three domains of executive functions (working memory, response inhibition, and vigilance) were assessed. In addition, five-minute eyes closed electroencephalography was obtained from some of the children with ASD and neurotypical children. DNA sequence and expression level of FOXP2 in blood samples of children with ASD and the control group were evaluated by using sequencing and Real-time PCR, respectively. Results: The results showed no mutations but a significant down expression of FOXP2 genes in children with ASD vs. neurotypical children. Several cognitive and executive function deficiencies were detected in children with ASD. Low alpha and gamma bands in the frontal lobe and high theta bands in the occipital lobe were revealed in children with ASD. We also found several correlations between FOXP2 expression levels and clinical assessments. Conclusions: Our finding revealed the down expression of FOXP2, which could be considered as a biomarker for ASD as well as cognitive and executive dysfunction. Based on brain mapping data, FOXP2 may be related to the theta wave abnormality of children with ASD. FOXP2 may be considered a target of novel treatment to improve memory and executive functions. Implications: Our findings highlight the role of FOXP2 mRNA level in ASD etiology, executive functions, and brain wave frequencies.